The importance of liver function assessment before cardiac surgery: A narrative review - Lopez-Delgado, Juan C.; Putzu, Alessandro; Landoni, Giovanni (Frontiers in Surgery, 2022)
The demand for cardiac surgery procedures is increasing globally. Thanks to an improvement in survival driven by medical advances, patients with liver disease undergo cardiac surgery more often. Liver disease is associated with the development of heart failure, especially in patients with advanced cirrhosis. Cardiovascular risk factors can also contribute to the development of both cardiomyopathy and liver disease and heart failure itself can worsen liver function. Despite the risk that liver disease and cirrhosis represent for the perioperative management of patients who undergo cardiac surgery, liver function is often not included in common risk scores for preoperative evaluation. These patients have worse short and long-term survival when compared with other cardiac surgery populations. Preoperative evaluation of liver function, postoperative management and close postoperative follow-up are crucial for avoiding complications and improving results. In the present narrative review, we discuss the pathophysiological components related with postoperative complications and mortality in patients with liver disease who undergo cardiac surgery and provide recommendations for the perioperative management.